Influencia de la temperatura en la producción de ácido indolacético por Bacillus subtilis en un biorreactor automatizado Bioflo - Celligen 115 - Salvatierra Espinola, Waldo Franz (2022)
Some environmental bacteria produce indoleacetic acid (IAA), which promotes root stimulation and promotes defense against phytopathogens. This phytohormone is regulated by environmental conditions such as temperature for its production. Therefore, the present research work was carried out, where the optimal temperature for the production of IAA from microbial fermentation in a Bioflo - Celligen bioreactor was evaluated, using a Bacillus subtilis strain. This strain was cultivated in Nutritive Broth liquid medium to obtain its growth curve at different temperatures and incubation times. IAA production was carried out evaluating different incubation temperatures (28, 29, 30 and 32 °C) in a completely randomized design. Regarding temperature, the influence of 28, 29, 30 and 32 ° C was evaluated in a completely randomized design. The yield of IAA obtained in each treatment to be determined by the colorimetric technique using the Salkowski reagent. Regarding the results, it was observed that IAA production reached a maximum concentration value of 0.92 mg/mL and 0.75 mg/mL at 18 hours of incubation at 30 °C and 28 °C, respectively. It is concluded that the temperature influenced the production of IAA by B. subtilis when it was subjected to fermentation processes in a Bioflo – Celligen 115 bioreactor.